Modeling of the Secondary System's Generated Interference and Studying of its Impact on the Secondary System Design - Ruttik, Kalle; Koufos, Konstantinos; Jantti, Riku (Společnost pro radioelektronické inženýrství, 2010)
In this paper we study how much capacity a cellular secondary system can achieve if the interference to the TV system is kept under control. The interference is modeled and controlled in a slow fading environment. The secondary system's capacity is computed for the adjacent and for the co-channel (with respect to the TV channel). We study the behavior of the system capacity while changing the size of the no transmission area surrounding the TV coverage area. It turns out that for most of the secondary cell sizes the network with adjacent channel is in interference limited mode and the network with co-channel is in noise limited mode. Since in the co-channel we can not use very high power it is recommended to use in bigger cells only adjacent channel.
Keywords: Secondary spectrum usage; interference; capacity